PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 – 2021 - Satria, Marta Ajie (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Equity, The aim of this study was to investigate how the stock prices of consumer goods companies listed on the Indonesia Stock Exchange are affected by the Return On Asset Ratio, Return On Debt to Equity Ratio, Earnings Per Share, and Dividend Per Share. The research technique used is a quantitative technique that makes use of numerical data. All consumer goods manufacturing companies registered on the Indonesia Stock Exchange make up the population of this study, but the sample in this study comprises of 25 companies chosen by purposive sampling. The yearly financial statements of the corporation from 2018 to 2021 are the secondary data used in this study. The data are analyzed using multiple linear regression, taking into account the conventional assumption test criteria of normality, multicollinearity, autocorrelation, and heteroscedasticity. The hypothesis is statistically examined using the SPSS for Windows version 25 program. The results of a partial test (t test) show that while debt to equity ratio and dividend per share have a significant impact on firm prices, ratios of return on equity, earnings per share, and return on assets have a significant impact on stock prices. The concurrent test results (F test) show that stock prices are significantly influenced by the independent variables (Ratio Return On Assets, Return On Equity, Debt to Equity Ratio, Earnings Per Share, and Dividends Per Share).